2018
DOI: 10.1177/1062860618792667
|View full text |Cite
|
Sign up to set email alerts
|

Provider-Focused Intervention to Promote Comprehensive Screening for Adolescent Idiopathic Scoliosis by Primary Care Pediatricians

Abstract: Screening can detect adolescent idiopathic scoliosis (AIS). The objective was to determine if computer-based simulation (CBS) and computerized clinical decision-support systems (CCDSS) would improve primary care providers' AIS screening exams as noted in their documentation. All participants received AIS screening CBS training. Participants were then randomized to receive either CCDSS when an eligible patient was seen (intervention arm) or no further intervention (comparison arm). Eligible patients' documentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…On the one hand, the extreme heterogeneity indicates non-random variation in effect sizes, such that a minority of interventions might have achieved significantly larger effects than the 95% confidence intervals around the meta-analytic average. Indeed, 25% of studies reported absolute improvements greater than 10%, with one as high as 62% 67. Yet, even with the identification of two significant predictors of larger effects—namely, paediatric studies and those with low baseline adherence—the meta-regression model still showed extreme heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, the extreme heterogeneity indicates non-random variation in effect sizes, such that a minority of interventions might have achieved significantly larger effects than the 95% confidence intervals around the meta-analytic average. Indeed, 25% of studies reported absolute improvements greater than 10%, with one as high as 62% 67. Yet, even with the identification of two significant predictors of larger effects—namely, paediatric studies and those with low baseline adherence—the meta-regression model still showed extreme heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, 25% of studies reported absolute improvements greater than 10%, with one as high as 62%. 67 Yet, even with the identification of two significant predictors of larger effects—namely, paediatric studies and those with low baseline adherence—the meta-regression model still showed extreme heterogeneity. Thus even when these characteristics were taken into account, a wide, non-random variation remained in the improvements seen with clinical decision support systems.…”
Section: Discussionmentioning
confidence: 99%